(untitled) (Journal of Technology and Operations Management, 2021)
Blockchain is a revolutionary technology that has provided the potential answers for many real-world problems in this digital era. Blockchain is a topic of immense interest in various industries and academia in terms of discovering technology and identifying challenges and innovative practical implementation for the industry. This study deliberates the challenges that are of major concern in designing a Blockchain platform. In this context, the problems such as inefficient technology design, the criminal connection, scalability, energy consumption, privacy, regulation, security, lack of adequate skill sets, energy consumption and public perception are uncovered to be significant. Due to such challenges, the blockchain technologies have emitted a negative impression due to its inabilities to be effectively implemented while, at the same time, its advantages could not be fully reaped by its stakeholders. The aim of this study, hence, is to evaluate the blockchain initiatives and development in light of the eight foundations for economic development as propounded by Ibn Khaldun. Using Ibn Khaldun’s theory, each challenge is discussed and analyzed to find the answers and solutions for addressing and overcoming the afore-mentioned challenges.